Pandemi Covid-19 dan Pengaruhnya terhadap Kebijakan Buyback Saham - Hana Tamara Putri; Ade Masyuri; R Adisetiawan (Universitas Batanghari Jambi, 2021)
The Covid-19 pandemic has caused the shares of issuers on the Indonesia Stock Exchange to plummet. Since the beginning of the year until the second week of October, the stock index on the Indonesia Stock Exchange has weakened to 19.52%. This price decrease is an opportunity for companies to buyback their shares in the capital market. Stock buyback policy is a repurchase of shares that have been issued by a company and owned by the company for a certain period of time that is a maximum of 3 years. Stock Buyback policy is a form of responsibility of the company carried out by the company with the aim to provide protection of the company's capital and wealth.